Clinical outcome measures to evaluate the effects of orthotic management post-stroke: a systematic review. Issue 13 (19th June 2022) - Ramstrand, Nerrolyn; Stevens, Phillip M.
Abstract: Purpose: To identify, and classify, according to International Classification of Functioning, Disability and Health (ICF), clinically applicable outcome measures that have been used to evaluate lower limb orthotic management post-stroke and to investigate which outcome measures recorded the largest effect sizes. Materials and methods: Electronic searches were performed in Pubmed, Cochrane, Web of Science, Cinahl, Scopus and Embase databases from inception to May 2020. Articles were included if they investigated clinical outcomes in people post-stroke who had received a lower-limb orthotic intervention. Results: 88 articles underwent full-text review and 54 were included in the review, which was performed in accordance with the Preferred Reporting Items for Systematic Review (PRISMA) principles. 48 different outcome measures were identified; effect sizes were able to be calculated from 39 studies. The most frequently applied outcome measures were the 10-metre Walk Test and the timed-up-and-go test. Outcome measures that recorded large effect sizes in two or more studies were the 10-metre Walk Test, Functional Reach Test, and Physiological Cost Index. When coded according to the ICF, the most frequently represented codes were d450 (Walking) and d455 (moving around). Conclusions: Results suggest that outcome measures related to mobility (ICF chapter d4) are most often applied to evaluate orthotic management post-stroke. Effect sizes appear to be greatest in outcome measures related to velocity, balance, and energy expenditure. IMPLICATIONS FOR REHABILITATION: The 10-meter Walk Test appears to have the greatest effect size when evaluating orthotic management post-stroke. While outcome measures related to mobility are commonly applied when evaluating orthotic management post-stroke, rehabilitation professionals should consider complementing these with measures representing the participation domain of the ICF.